STATISTICAL EVALUATION OF PERFORMANCE AND TRAINING SATISFACTION AT THE POLICE TRAINING ACADEMY, WUDIL - Musa, Yakubu; Muhammad, Falalu (FUDMA JOURNAL OF SCIENCES, 2025)
This survey research examines the determinants affecting academic achievement and training satisfaction among cadets at the Nigeria Police Academy in Wudil, Kano. The investigation evaluated the relationships between study habits and academic performance (quantified by CGPA), the effect of academic challenges on CGPA, the association between training satisfaction and perceived training relevance, the influence of preferred training methodologies, and the determinants affecting overall satisfaction with academic and training experiences. Statistical analysis indicated a strong positive correlation between study hours and CGPA (r=.311, p
Keywords: Police Academy, Chi-Square Test, Logistics Regression, Nigeria; Police Academy; Chi-Square Test; Logistics Regression; Nigeria